Laboratory parameters of COVID-19 patients in Khulna, Bangladesh (Bangladesh Medical Journal Khulna, 2021)
Background: Recent studies have demonstrated the role of several laboratory tests in addition to RT-PCR in the diagnosis of COVID 19. Some of these, laboratory tests are indicators of the current state of the disease, while others have proved to be useful prognostic markers.Objective: The objective of our study was to evaluate the hematological, biochemical and radiological changes in COVID-19 patients.Methods: It was an observational and analytical study done retrospectively. The whole number of patients were included on the basis of inclusion and exclusion creteria. All were confirmed cases of COVID-19 patients either admitted in different hospitals or were in home isolation.Results: Total study cases was 112. Complete blood count revealed, leukocytosis was present in 9 (8.0%) cases and leucopenia in 8 (7.14%) cases. Neutrophilia was present in 27 (24.1%) cases; neutropenia in 9(8.0%) cases, lymphocylosis in 17 (15.2%) cases; lymphopenia in 28 (25%) cases. Neutrophil Lymphocyte ratio (NLR) revealed mean value of NLR 2.3(±1.1) with a range of 0.6-4.0. Decreased total circulating eosinophil count (